VALUASI HARGA SAHAM PADA PERUSAHAAN SUB SEKTOR MAKANAN DAN MINUMAN - Faisal, Yusuf; Adinda Elta, Nicholla Anggelita (Fakultas Ekonomi dan Bisnis Universitas Alma Ata, 2024)
The study aims to determine the effect of Return On Equity, Debt to Equity Ratio, Dividen Payot Ratio, and Price to Book Value on Price Earnings Ratio. This research uses quantitative data, the sample in ithis study is food and bavarage sub sector companies which are listed on the Indonesian Stock Exchange in the period 2017-2022 as many 15 companies. The analysis technique used to test the hypothesis is multiple regression analysis using Eviews 9 software. The results of this study indicate that the Return on Equity variable has positive and statistically effect on price to earnings ratio, the Debt to Equity Ratio variable has a negative and statistically insignificant effect on price to earnings ratio, the Dividend Payout Ratio has positive and statistically effect on price to earnings ratio, and the Price to Book Value has positive and statistically not insignificant effect on price to earnings ratio. This study discusses Price Earnings Ratio and other factors such as Return on Equity, Debt to Equity Rati0, Dividend Payout Ratio, and Price to Book Value which focuses on the research year and sample size on food and bavarage sub sector companies